Developing A Hybrid Model For Remanufacturing Facility Location Problem In A Closed Loop Supply Chain - Zulkifli, Norzima; Alimoradi, A.; Yusuff, R. M. (2011)
In today’s competitive environment, the movement of raw materials to processing units, components assembly plants, and finished goods plants throughout the supply chain are crucial. On the other hand, design of supply chain is usually based on an open loop configuration or forward flow of materials, which means that the recent attentions from governments, manufacturers, and customers for recovery of materials are not considered in supply chain in spite of their importance. In our research, we are going to design a closed loop supply chain constituted of suppliers, manufacturing plants, warehouses and distribution centers, customers or retailers (which are characteristics that form the generic configuration of facility location problem), and also we add new concepts of recovery centers, and remanufacturing plants and try to find the optimized location for these facilities in a discrete space. In uncapacitated facility location problems (UFLP), there are usually uncertainties about future factors such as customer demand, price of land, pool of expert labor, government’s regulations, and other factors which put restrictions on decision making about facility locations. To cope with the vagueness’s of factors; we will implement the concepts of artificial intelligence, and will use the fuzzy sets to simulate restrictions of our suggested new facility location decision which consist two new tiers and use them to solve the problem. Since our main object is to locate new facilities, fuzzy TOPSIS methodology will be implemented to find the best place.